(untitled) (Swiss Medical Weekly, 2025)
INTRODUCTION: Inappropriate antibiotic prescribing drives antimicrobial resistance. Although the Swiss Society of Infectious Diseases has introduced national guidelines for common infectious diseases starting from 2019, it remains unclear whether family physicians and paediatricians adhere to them and what factors influence their prescriptions. The aims of this study were to assess whether Swiss family physicians and paediatricians make appropriate antibiotic choices in accordance with national guidelines and to identify physician- and patient-related factors associated with the prescribing of not-recommended antibiotic choices for specific indications. METHODS: A cross-sectional study analysed the choice of antibiotics (2017–2022) by indication from a sentinel physician surveillance network, comparing them to adult (16+) and paediatric national guidelines. Indications included pharyngitis, sinusitis, otitis media, pneumonia, chronic obstructive pulmonary disease exacerbation (adults only) and upper and lower urinary tract infections (adult females only). Descriptive analysis and pre- and post-guideline comparisons were conducted. A multilevel logistic regression model assessed factors influencing prescribing of not-recommended antibiotics across several clinical indications. RESULTS: A total of 52,098 observations were analysed. The overall proportion of not-recommended antibiotic prescriptions was 18% for adults and 19% for children. The proportion of not-recommended antibiotics ranged from 8% (lower urinary tract infection) to 39% (sinusitis) in adults, and from 5% (sinusitis) to 38% (pharyngitis) in children. The proportion of not-recommended antibiotics decreased following guideline implementation for all indications for children and for sinusitis (48% vs 39%) and pneumonia (19% vs 15%) for adults. A multilevel model revealed that certain clinical indications – such as pharyngitis – were associated with higher odds of prescribing not-recommended antibiotics. Additionally, family physicians (compared to paediatricians), older physician age and physicians’ perception of a favourable patient attitude to the antibiotic were also linked to increased prescribing of not-recommended antibiotics. CONCLUSIONS: Swiss family physicians and paediatricians show high levels of non-adherence to national guidelines across several indications, with limited change post-guideline implementation. Certain demographic characteristics of physicians and patient behaviour exacerbate these inappropriate prescribing habits. These insights indicate the need to enhance guideline dissemination and adoption by considering physicians’ needs.